Pelatihan Sertifikasi Halal dan Pemasaran Modern untuk Meningkatkan Pendatan Usaha Makanan di Desa Maringgit - Sri Maulida; Haifa Lestari; Akhsanul Rahmatullah; Saipudin, Saipudin; Muhammad Saleh (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The growth of MSMEs has been steadily increasing each year, yet they still face various challenges. One of the sectors contributing the most to the national economy is the food and culinary industry. MSMEs in Maringgit Village sell traditional foods from the Hulu Sungai Tengah region, such as kue cincin, rice cakes, kue apam, kue jabuk, sugar-coated peanuts, and other processed foods. Increasingly fierce competition has made it difficult for them to compete due to limited knowledge of how to increase income and sales. This study focuses on how MSMEs in Maringgit Village can boost their income through halal certification and modern marketing. The lack of information and knowledge has caused business owners to misunderstand regulations governing halal certification. Therefore, outreach and assistance with halal product certification are crucial to help these products enter modern markets. This community service aims to help MSMEs in Maringgit Village overcome these challenges. The assistance in halal certification and modern marketing training is carried out in stages, both online and offline. Success indicators were tested using difference tests. The results of this community service show that the knowledge and income of MSME food producers in Maringgit Village significantly increased after participating in the training. Income increased by 122%, with statistical results showing a significant change with a very strong correlation. Knowledge increased by 60%, with statistical results showing a significant change with a strong correlation.